Neonatal erythematous lupus - Kecelj, Nada (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2003)
An infant with annular erythemas, which appeared soon after birth, is presented. The laboratory tests revealed mild anaemia and high values for anti-Ro/SS-A, and anti-La/SS-B antibodies. Routine histology and direct immunofluorescence microscopy examination confirmed the diagnosis of neonatal lupus erythematosus (NLE). The skin lesions resolved completely in the first six months of life. No cardiac abnormalities were detected during the follow-up and no systemic therapy was necesary. Sun protection was recommended. The baby's mother was asymptomatic during pregnancy and also for some months after it. One year later she developed sicca symptoms (mb Sjoegren).
Keywords: Antibodies, Antinuclear; Autoantibodies; Avtoprotitelesa; baby; dermatologija; Dojenček; dojenčki; Infant; kožne bolezni; Lupus eritematozni, kožni; Lupus Erythematosus, Cutaneous; Protitelesa protijedrna